2021
DOI: 10.1007/s11357-021-00467-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the SARS-CoV-2 cellular receptor ACE2 levels in cardiovascular patients: a potential biomarker for the stratification of COVID-19 patients

Abstract: Angiotensin-converting enzyme 2 (ACE2) is essential for SARS-CoV-2 cellular entry. Here we studied the effects of common comorbidities in severe COVID-19 on ACE2 expression. ACE2 levels (by enzyme activity and ELISA measurements) were determined in human serum, heart and lung samples from patients with hypertension (n = 540), heart transplantation (289) and thoracic surgery (n = 49). Healthy individuals (n = 46) represented the controls. Serum ACE2 activity was increased in hypertensive subjects (132%) and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In patients with comorbidities that affect the microvasculature or the myocardium, COVID-19-related vascular and myocardial pathologies can be exacerbated. Furthermore, both aging and several comorbidities were shown to increase the expression of the cellular entry receptors of SARS-CoV-2, which directly affect the severity of COVID-19 [49][50][51][52]. A possible entry receptor of COVID-19 could also be the adipokine enzyme DPP4 [53].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with comorbidities that affect the microvasculature or the myocardium, COVID-19-related vascular and myocardial pathologies can be exacerbated. Furthermore, both aging and several comorbidities were shown to increase the expression of the cellular entry receptors of SARS-CoV-2, which directly affect the severity of COVID-19 [49][50][51][52]. A possible entry receptor of COVID-19 could also be the adipokine enzyme DPP4 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recruiting COVID-19 patients was approved under the registration number 32568-32020EÜIG [ 11 ]⁠. Recruiting patients with heart failure with dilated cardiomyopathy [ 12 ]⁠ or with aortic stenosis [ 13 ]⁠ was approved under the registration identifier UDCC RECIEC 4375–2015. The human heart samples used for the identification of the autoantibodies were collected and banked under the cover of an ethical permit issued by the Hungarian Ministry of Health (323–82,005-1018EKU).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that COVID-19 can affect individuals in all age groups, yet it mostly causes severe disease in older adults. The mechanisms by which aging exacerbate the severity of COVID-19 include age-related immunosenescence, aging-induced impairment of organismal and cellular stress resilience and a greater prevalence of comorbidities in older adults [2,[12][13][14][15][16][17][18][19][20][21][22][23][24]. COPD patients who are former smokers tend to exhibit the highest mortality associated with COVID-19 infection [15][16][17].…”
Section: Copd Exacerbates Severity Of Covid-19mentioning
confidence: 99%
“…On the basis of the available evidence it can be hypothesized that changes in the expression of ACE-2 play an important role in increased susceptibility to severe COVID-19 infection. ACE-2 is implicated in the entry of the virus into the host's airway epithelium to establish an active infection [18,19]. A recent clinical trial was conducted to explore the association between ACE-2 expression and COVID-19 mortality in COPD patients [20].…”
Section: Copd Cigarette Smoking and Ace-2 Expressionmentioning
confidence: 99%